III‐V//CuxIn1−yGaySe2 multijunction solar cells with 27.2% efficiency fabricated using modified smart stack technology with Pd nanoparticle array and adhesive material. (16th May 2021) - Makita, Kikuo; Kamikawa, Yukiko; Mizuno, Hidenori; Oshima, Ryuji; Shoji, Yasushi; Ishizuka, Shogo; Müller, Ralph; Beutel, Paul; Lackner, David; Benick, Jan; Hermle, Martin; Dimroth, Frank; et al.
Abstract: Multijunction (MJ) solar cells achieve high efficiencies by effectively utilizing the solar spectrum. Previously, we have developed III‐V MJ solar cells using smart stack technology, a mechanical stacking technology that uses a Pd nanoparticle array. In this study, we fabricated an InGaP/AlGaAs//Cu x In1− y Ga y Se2 three‐junction solar cell by applying modified smart stack technology with a Pd nanoparticle array and adhesive material. Using adhesive material (silicone adhesive), the bonding stability was improved conspicuously. The total efficiency achieved was 27.2% under AM 1.5 G solar spectrum illumination, which is a better performance compared to our previous result (24.2%) for a two‐terminal solar cell. The performance was achieved by optimizing the structure of the upper GaAs‐based cell and by using a Cu x In1− y Ga y Se2 solar cell with a specialized performance for an MJ configuration. In addition, we assessed the reliability of the InGaP/AlGaAs//Cu x In1− y Ga y Se2 three‐junction solar cell through a heat cycle test (from −40°C to +85°C; 50 cycles) and were able to confirm that our solar cells show high resistivity under severe conditions. The results demonstrate the potential of III‐V//Cu x In1− y Ga y Se2 MJ solar cells as next‐generation photovoltaic cells for applications such as vehicle‐integrated photovoltaics; they also demonstrate the effectiveness of modified smart stack technology in fabricating MJ cells. Abstract : We fabricated an InGaP/AlGaAs//Cu x In1− y Ga y Se2 three‐junction solar cell by applying modified smart stack technology with a Pd nanoparticle array and adhesive material. The total efficiency was 27.2% under AM 1.5 G. The performance was achieved by optimizing the structure of the upper GaAs‐based cell and applying a Cu x In1− y Ga y Se2 solar cell with high performance specialized for a multijunction (MJ) configuration. The results demonstrate the potential of III‐V//Cu x In1− y Ga y Se2 ‐based MJ solar cells as next‐generation photovoltaic cells for applications such as vehicle‐integrated photovoltaics.